WILL GIVE BRAINLIEST IF FAST!! GIVE GOOD REVIEWS FOR CORRECT ANSWERS!
![WILL GIVE BRAINLIEST IF FAST GIVE GOOD REVIEWS FOR CORRECT ANSWERS class=](https://us-static.z-dn.net/files/d67/040637248c5707aa4b048555e49424a5.png)
Step-by-step explanation:
The common ratio is - 2/3 because -2 * - 2/3 = 4/3
so each term is -2/3 times the preceding term
an = a1*( - 2/3) ^(n-1) a1 = -2
then the 6th term is
a6 = -2 ( -2/3)^5 = 64/243
Answer:
Step-by-step explanation:
-2 and -2/3
And 6th term is 64/24
Answer:
Step-by-step explanation:
-2 and -2/3
And 6th term is 64/24